Old wounds - Kisner, Logan-Ashley (Delacorte Press, 2024)
Two transgender teens end up in a small, isolated town, where they must escape the locals who plan to sacrifice one of them to an ancient monster that only eats girls. A pulse-pounding thriller perfect for fans of Midsommar and Hell Followed with Us! Erin and Max are two transgender teens trying to get to California. Max is desperate to finally transition, and Erin is longing to understand why she’s on this trip to begin with. The last she spoke to Max was when he suddenly broke up with her two years ago. But when they find themselves stranded in the middle of the woods in a small Kentucky town, they realize they have much bigger problems. The locals need a female sacrifice for the monster that lives in the woods--according to them, the sun won’t come up again until the monster eats a girl . . . and it only eats what it kills. Fighting back is futile; no one selected as the offering has ever survived the night. When the two strangers show up, the locals believe they have the perfect candidate. The irony of the situation is almost too much to fathom. The thing is, the locals don’t know who they just trapped as their sacrifice. They don’t know Erin’s and Max’s secrets, which could be a death sentence on a good day. And the monster that lives in their woods has never faced prey who have already fought so hard to live.